ANALISIS KESULITAN PELAKSANAAN PENILAIAN AUTENTIK DALAM PEMBELAJARAN BIOLOGI PADA KURIKULUM 2013 DI SMA NEGERI KOTA BINJAI - Nurlian Agustun Ningrum; Ashar Hasairin (Jurnal Pelita Pendidikan, 2018)
This study aims to determine the difficulties of authentic assessment experienced by biology teachers in public high schools in the city of Binjai. This research is descriptive with quantitative and qualitative analysis. The sample in this research is 18 biology teacher taken by using purposive sampling technique. Data collection techniques are by filling in questionnaires, interviews, documentation and direct observation. The results showed that some of the biology teachers of SMA Negeri in Binjai City experienced obstacles while carrying out authentic assessment. Constraints faced by biology teachers include difficulties in instrument making, difficulties in filling out the assessment format, difficulty in assessing students' attitudes objectively. There are several factors that cause teachers to experience constraints when carrying out authentic assessment that is the number of students who are not ideal, lack of understanding of authentic assessment procedures, training and socialization of authentic assessment has not been maximal, facilities and infrastructure of schools that are less supportive. The difficulty level faced by teachers in the implementation of authentic assessment is quite difficult with the value of 61.01.Keywords: teacher constraints, authentic assessment, biology learning.